2012
DOI: 10.1016/j.heares.2012.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of cochlear implant performance by genetic mutation: The spiral ganglion hypothesis

Abstract: Background Up to 7% of patients with severe-to-profound deafness do not benefit from cochlear implantation. Given the high surgical implantation and clinical management cost of cochlear implantation (> $1 million lifetime cost), prospective identification of the worst performers would reduce unnecessary procedures and healthcare costs. Because cochlear implants bypass the membranous labyrinth but rely on the spiral ganglion for functionality, we hypothesize that cochlear implant (CI) performance is dictated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
120
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(134 citation statements)
references
References 81 publications
8
120
1
5
Order By: Relevance
“…The study with the lowest diagnostic rate, Eppsteiner et al 2012, focused on adults with hearing loss and therefore may have had an ascertainment bias towards individuals with environmental or noise-induced non-genetic hearing loss 16 . Gu et al 2014, found a diagnostic rate of 13%, however the patients were strictly pre-screened and were all sporadic patients with no family history of hearing loss 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The study with the lowest diagnostic rate, Eppsteiner et al 2012, focused on adults with hearing loss and therefore may have had an ascertainment bias towards individuals with environmental or noise-induced non-genetic hearing loss 16 . Gu et al 2014, found a diagnostic rate of 13%, however the patients were strictly pre-screened and were all sporadic patients with no family history of hearing loss 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The mutations of p.E1957X and c.879+1G>A were novel and p.R1494X had been reported in an American family [13]. LOXHD1 expresses along the plasma membrane of stereocillia.…”
Section: Discussionmentioning
confidence: 99%
“…In DFNX2, the conductive component is atypical; the intracochlear source of the air-bone gap could alter the middle ear and cochlear transfer functions with implications for amplification algorithms, but this has not been investigated in patients with POU3F4 mutations (Petersen et al, 2008;Tang & Parnes, 1994). A more comprehensive understanding of the genotypephenotype correlations associated with different hearing loss etiologies could drive the development of alternative amplification algorithms and also be useful for predicting success with cochlear implantation (Eppsteiner et al, 2012).…”
Section: Implications For Clinical Practicementioning
confidence: 99%